2014
DOI: 10.1590/0102-33062014abb3158
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of Anathallis adenochila (Loefgr.) F. Barros (Orchidaceae), a species endemic to southern and southeastern Brazil

Abstract: Anathallis adenochila is a small epiphytic orchid, endemic to the Atlantic Forest in the southern and southeastern regions of Brazil. Information on the species is scarce and limited to distribution and occurrence data, with no reports about its development. In the present study, plantlets were propagated in vitro, and the influence of different concentrations of macronutrient salts and sucrose on the survival and development of the species was assessed. The analysis were performed on complete Murashige and Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Other than that, to further support the results as seen in Figure 1 , in the same study, the inability of maltose to produce PLBs was also reported in the study Sanjaya et al (2007). On top of that, the same sucrose concentration which is 30 g/L was also found out to be optimal for protocorms development of orchids were reported by Júnior et al (2014) which further verify the results obtained from this study.…”
Section: Resultssupporting
confidence: 88%
“…Other than that, to further support the results as seen in Figure 1 , in the same study, the inability of maltose to produce PLBs was also reported in the study Sanjaya et al (2007). On top of that, the same sucrose concentration which is 30 g/L was also found out to be optimal for protocorms development of orchids were reported by Júnior et al (2014) which further verify the results obtained from this study.…”
Section: Resultssupporting
confidence: 88%
“…For example, Anathallis adenochila (Loefgr.) F. Barros was found to take 12 months to develop seedlings (> 0.5 cm in height) [ 21 ]. In another species of the Pleurothallidinae subtribe, Restrepia brachypus Rchb.f., germination ranged from 7.96% in MS medium to 53.05% in Western (W) medium [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most species of Pleurothallidinae have no great commercial appeal, due to the small dimensions of the plants and their flowers, as well as the difficulties of cultivation [ 18 ]. There are few studies of asymbiotic germination of micro-orchids, which have shown low germination rates and slow growth of seedlings [ 21 , 22 ]. The best results were achieved by Koene et al [ 13 ] with 79% of total germination of A .…”
Section: Introductionmentioning
confidence: 99%
“…It could be noted that Brazil has the highest number of published works both on propagation and germplasm conservation, while for some countries only researches referring to propagation of native orchid species are reported and for other countries (Guyana, Paraguay, Trinidad and Tobago, Suriname, Uruguay) there were no registered works in any of the topics. Almeida et al 2017;Caovila et al 2016;Cardoso and Ono 2011;Cavalcante Martini et al 2001;Corrêa Pereira et al 2011;2015;Da Silva et al 2014;Da Silva Júnior et al 2012;De Carvalho et al 2018;De Conti et al 2018;De Melo Ferreira et al 2017;De Menezes Gonçalves et al 2012;Dezan et al 2012;Dignart et al 2009;Dorneles and Trevelin 2011;Endres Júnior et al 2014;Favetta et al 2017;Galdiano Júnior et al 2011;2012a,b;Gomes de Araújo et al 2009;Hosomi et al 2017;Lando et al 2016;Lone et al 2010;Mantovani et al 2016;Massaro et al 2012;Monteiro do Rêgo et al 2009;Moraes et al 2005;Pasqual et al 2011;Pedroso-de-Moraes et al 2012;Pereira et al 2018;Pereira Gomes et al 2015;Prizão et al 2012;Rodrigues et al 2015;Rodrigues Guimarães et al 2013;Sasamori et al 2015;…”
Section: In Vitro Conservation Approaches In Orchidsmentioning
confidence: 99%